International Coordination of Fiscal Policies : A Review of Some Major Issues. (IMF Working Papers; Working Paper, 1988)
International coordination of macroeconomic policies has attracted much attention in recent years. The main issue has been whether economic performance can be improved by coordination Although it is still a controversial issue many economists have argued that coordination would make a positive contribution to economic performance. This paper deals with the requirements for successful fiscal coordination. It concludes that those requirements are such that the best fiscal policies that countries can pursue are those aimed at putting their houses in order.